Comparison of carrier proteins to conjugate malaria transmission blocking vaccine antigens, Pfs25 and Pfs230. Issue 34 (22nd July 2020) - Scaria, Puthupparampil V.; Chen, Beth B.; Rowe, Christopher G.; Alani, Nada; Muratova, Olga V.; Barnafo, Emma K.; Lambert, Lynn E.; Zaidi, Irfan U.; Lees, Andrew; Rausch, Kelly M.; Narum, David L.; Duffy, Patrick E.
Abstract: Malaria transmission blocking vaccines (TBV) target the sexual stage of the parasite and have been pursued as a stand-alone vaccine or for combination with pre-erythrocytic or blood stage vaccines. Our efforts to develop TBV focus primarily on two antigens, Pfs25 and Pfs230. Chemical conjugation of these poorly immunogenic antigens to carrier proteins enhances their immunogenicity, and conjugates of these antigens to Exoprotein A (EPA) are currently under evaluation in clinical trials. Nonetheless, more potent carriers may augment the immunogenicity of these antigens for a more efficacious vaccine; here, we evaluate a series of proteins to identify such a carrier. Pfs25 and Pfs230 were chemically conjugated to 4 different carriers [tetanus toxoid (TT), a recombinant fragment of tetanus toxin heavy chain (rTThc), recombinant CRM197 produced in Pseudomonas fluorescens (CRM197) or in E. coli (EcoCRM®)] and compared to EPA conjugates in mouse immunogenicity studies. Conjugates of each antigen formulated in Alhydrogel® elicited similar antibody titers but showed differences in functional activity. At a 0.5 µg dose, Pfs230 conjugated to TT, CRM197 and EcoCRM® showed significantly higher functional activity compared to EPA. When formulated with the more potent adjuvant GLA-LSQ, all 4 alternate conjugates induced higher antibody titers as well as increased functional activity compared to the EPA conjugate. IgG subclass analysis of Pfs230 conjugates showed no carrier-dependent differences in the IgG profile. While Alhydrogel® formulations induced a Th2 dominant immune response, GLA-LSQ formulations induced a mixed Th1/Th2 response.